Structural, microstructural and electrical characterization of Sr1-xCeO3: xNa+ (0 ≤ x ≤ 0.08): Investigating dielectric relaxation and NSPT charge transport mechanism - Tripathi A.; Kumar P.; Verma H.; Upadhyay S. (My University, 2025)
This investigation emphasizes monovalent substitution of Na+ ions at Sr- sites of SrCeO3. Three compositions (x = 0.00, 0.04, and 0.08) of the Sr1-xCeO3: xNa+ system named NS0, NS4, and NS8 were synthesized using a solid-state reaction route. XRD and Rietveld refinement confirmed their orthorhombic structure within the Pnma space group. SEM was employed to assess the impact of dopant on the microstructure, showing grain size enlargement attributed to sodium as a sintering aid in the doped samples. XPS showed the presence of Ce4+ and Ce3+ states. The Kubelka-Munk equation was employed to measure the bandgap reduction on Na+ doping. To get insight into dielectric and electrical properties, mesurements were thoroughly analyzed in RF range with temperature range 300–600 ℃. NS8 shows higher dielectric constant and lower dissipation factor. The frequency exponent variation with temperature agrees with the NSPT model. Impedance spectroscopy revealed two relaxation phenomena associated with the grain and grain boundaries. © 2025 Elsevier B.V.